Un "boxing" the reality: Knowledge, attitude, and perception of orthodontists, dental practitioners, and orthodontic patients toward mouthguards' wear during contact sports-A cross‐sectional study - Shailaja Raghavan; Elham S. Abu Alhaija; Yousef Nasrawi; Susan Al‐ Khateeb; Samer Sunna (Wiley, 2024)
Abstract Introduction Mouthguards (MGs) have the potential to prevent contact sport‐related dental injuries. However, varying perceptions of their effectiveness persist, influencing recommendations by dental professionals. Aim To assess the attitudes, knowledge, and perceptions of orthodontists, other dental practitioners (general dentists and other dental specialists), and orthodontic patients involved in contact sports regarding the use of MGs. Methodology A cross‐sectional survey was designed to collect information from dental clinicians (orthodontists and other dental practitioners) and their orthodontic patients about using MGs during sports participation. A convenience sampling technique was used to recruit the participants for an online survey. A total of 107 (32 males/75 females) dental clinicians and 147 (75 males/72 females) orthodontic patients (mean age 17.5 ± 5.84 years) participated in the study. Pre‐validated questionnaires, specifically designed for dental clinicians and orthodontic patients, were used. Data were analyzed using SPSS software (version 28.0; SPSS). Results Nearly 50% of dental clinicians have recently recommended MGs to their patients in their clinical practice out of which 59% preferred the stock type; 33% of dental clinicians enquired their patients about involvement in contact sports during initial visits. The majority of orthodontic patients acquired knowledge about MGs through the Internet. More than half of orthodontic patients expressed unwillingness to pay for MGs, and 89% of orthodontic patients found using MGs during contact sports uncomfortable. Conclusion The findings provide valuable insights into the practices and attitudes of dental clinicians and orthodontic patients regarding MGs, their recommendations, and the comfort levels associated with using them during contact sports.